Use of Carbon Nano Particles in Concrete - Kumar, Mr. Sameer; Kumar, Dr. Ajay (International Journal on Orange Technologies, 2025)
Over the past 100 years, RCC has been used in construction projects. RCC has been used most extensively in India for the past 50–60 years. We have built a great deal of infrastructure over this time, including buildings, bridges, sports stadiums, and other structures that are essential to a civilized society. These were created with massive resource speculation. Not even the notion of developing such resources from our meager national resources can occur to us. Therefore, keeping them in operational condition is crucial. This study investigated how to improve the mechanical properties of Portland cement concrete as a building material by utilizing nanotechnology-based nano-elements, such as carbon nanotubes (CNTs) & nanofibers (CNFs), as reinforcement or filler. CNTs and CNFs have been used as excellent R/Fs in enhancing the mechanical and physical properties of polymer, metallic, and ceramic composites because of their extremely high aspect ratios and ultra-high strength. The application of nano-elements in the building sector has received very little research attention. Consequently, the goal of this thesis was to close the knowledge gap between nanomaterials and building supplies. This was accomplished by utilizing cutting-edge methods to test the incorporation of CNTs and CNFs in regular Portland cement paste. Various mixes with varied concentrations of CNTs or CNFs were prepared in fixed proportions (e.g., water-to-cement ratio, air content, admixtures). Various methods that are frequently employed in current research to assess the CNTs' strength CNT strengths are ascertained by running the cube analysis test, entering the results into the Etabs Model, and comparing the results to find the difference. After Test & Evaluation on CNTs cube test results with adding of 0.2wt.% by weight of cement, create a computer-based software model & compare normal strength as well as Strength with carbon nanotubes (CNTs) & nanofibers (CNFs). Also, all possible compare taken care like base share match, R/F consumption, cost analysis, etc.